Comparative estimation of a pain syndrome in patients after combined operations for coexistent pathology of anal channel and rectum with application of modern and standard surgical technologies - V. V. Balytskyy (Клінічна хірургія)
Objective. Comparative estimation of the pain syndrome in patients with concomitant pathology of anal channel and rectum after performance of combined operations, using modern high-frequency electro-surgical and radio-surgical apparatuses, as well as conventional scalpel.